PM.90 Incidental Phaeochromocytoma in Pregnancy. (26th April 2013) - Chen, BF; Al-Samarrai, S; Rathi, M; Rajeswary, J
Abstract : Introduction: Phaeochromocytoma, a catecholamine-producing endocrine tumour, is a life-threatening condition to the mother and fetus. The incidence of phaeochromocytoma in pregnancy is extremely rare, 1 in 54 000 pregnancies 1 . If it remains undiagnosed and untreated, maternal and fetal mortality amounts to 40–50% 2 3 . Classically, physicians search for the tumour in hypertensive patients with paroxysmal symptoms such as headache, sweating or palpitations. However, our patient presented atypically and would have been left undiagnosed. Case presentation: A 21-year-old presented after a fall at 24 weeks gestation, with loin pain on the contralateral side to the fall. This prompted an ultrasound scan that demonstrated a 9 cm 'haematoma' above the right kidney. As she was claustrophobic, she declined magnetic resonance imaging (MRI). A repeat ultrasound was performed which showed the mass to be unchanged. Suspicion arose and an MRI under sedation was performed (as recommended to look for adrenal/renal mass in pregnancy 4 ). This confirmed an 8 cm × 7 cm mass superior to the right kidney. An endocrinologist reviewed her and serum and urine biochemistry investigations were performed. Her urinary 3-methoxytyramine and serum dopamine levels were raised 5 6 indicating possible phaechromocytoma. She did not need α-adrenoceptor blockade, as she remained asymptomatic throughout her pregnancy. She was referred to a tertiary hospital where an elective Caesarean section and surgical tumour removal were performed simultaneously. Conclusion: Diagnosing phaeochromocytoma in an asymptomatic pregnant patient is challenging. However, when diagnosed, a multi-disciplinary team approach (obstetrician, surgeon and endocrinologist) is vital in the management of this rare disorder. References: Lenders JWM. Phaeochromocytoma and pregnancy: a deceptive connexion. European Journal of Endocrinology 2012;161:143–150. Schenker JG & Chowers I. Phaeochromocytoma and pregnancy. Review of 89 cases. Obstetrical and Gynecological Survey 1971;26:739–747. Dean RE. Phaeochromocytoma and pregnancy. Obstetrics and Gynecology 1958;11: 35–42. Lenders JW, Eisenhofer G, Mannelli M, et al . Phaeochromocytoma. Lancet 2005;366:665–675. Peleg D, Munsick RA, Diker D, Goldman JA & Ben-Jonathan N. Distribution of catecholamines between fetal and maternal compartments during human pregnancy with emphasis on L-dopa and dopamine. Journal of Clinical Endocrinology and Metabolism 1986;62:911–914. Lenders JW, Pacak K, Walther MM, Linehan WM, Mannelli M, Friberg P, Keiser HR, Goldstein DS & Eisenhofer G. Biochemical diagnosis of phaeochromocytoma: which test is best? Journal of the American Medical Association 2002;287: 1427–1434.